Absorptive and desorptive capacity of actors within university-industry relations: Does technology transfer matter? - Davide DellÁnno; Manlio Del Giudice (Journal of Innovation and Entrepreneurship, 2015)
Several management studies highlight the importance of collaborative relationships for university-industry knowledge and technology transfer. The present study examines the role of absorptive and desorptive capacity (A/DCAP) of actors in technology transfer processes by pointing out critical elements that may affect regional innovation systems. In this field of action, each university worldwide, as well as public and private research centers, interacts differently with industry. Cultural and economic variances make it difficult to outline one single global model governing knowledge and technology transfer. However, it is possible to identify elements and characteristics that might make this system efficient. Mere interaction is a necessary but not a sufficient condition to ensure that knowledge and technology flow through a feasible dyadic channel from university to industry (U-I) or vice versa (I-U). Indeed, the actors of the process have to develop organizational capabilities at all levels and units (i.e., individual and organizational) based on a social integration system which can facilitate their communication, thus helping to share activities. In this regard, we present a systematic review of research into academic involvement in the regional innovation development environment by identifying individual as well as organizational and institutional layers of this crossrelationship. Apart from being more widely applied, A/DCAP is strictly important for academics in order to access resources and results able to support their research agendas.
Keywords: 650; Absorptive capacity; Desorptive capacity; Knowledge transfer; Technology transfer; Organizational culture; University-industry relation